Perlindungan Hukum Kawasan Hutan Adat dan Hak Ulayat - Obed Edotalino Sudiro; Slamet Suhartono (Politika Progresif : Jurnal Hukum, Politik dan Humaniora, 2024)
The increasingly rapid development of the times has opened people's views to be more open to various kinds of world and national problems. Technology, which is one of the tools for thinking, has created innovative patterns of thinking in society that are mature in determining diverse perspectives and actions, as well as every outcome of views and attitudes that is permitted as long as it does not violate the rules and norms that have been regulated in state life. Customary forests are one of the categories of social forestry which are located in the living areas of local indigenous communities and can usually be found in inland areas. Customary forests are also regulated in Law Number 41 of 1999 concerning Forestry as stated in Article 1 number 6 "Customary forests are state forests that are within the territory of customary law communities." Conflicts between company interests and the rights of indigenous communities sometimes arise due to a lack of legal protection and unequal power, this is based on expansion which can be said to be irregular because quite a few mining companies expand mining areas outside the mine itself in order to exploit very natural resources. abundant in it.